2017
DOI: 10.1590/0103-656420140011
|View full text |Cite
|
Sign up to set email alerts
|

Concepções homofóbicas de estudantes do ensino médio

Abstract: This paper presents the results of a study carried on with 2,159 male and female high school students from three cities in the countryside of São Paulo State, Brazil. The data obtained by a Likert scale were analyzed by a multivariate statistical technique. Regarding the factor analysis, the method used for extracting the factors was the major component and oblique rotation method, in which the six factors obtained aid to interpreting the possible correlations among the homophobic views presented in items. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
0
1
0
16
Order By: Relevance
“…The participants expressed antagonistic behaviors: at times they were victims of different forms of violence; at others, they were perpetrators, an aspect perceived in their expressions of homophobia. Homophobia is a social, historical, community, family, and religious construction, which, sustained by misogynistic and sexist ideals, strengthens heteronormative ideas that impose relationships of power and knowledge about the sexes 24 . One study that investigated the homophobic conceptions of adolescents found moderate tolerance to homosexuality 25 obtidos pelo uso de uma escala Likert, foram analisados por uma técnica estatística multivariada.…”
Section: Discussionmentioning
confidence: 99%
“…The participants expressed antagonistic behaviors: at times they were victims of different forms of violence; at others, they were perpetrators, an aspect perceived in their expressions of homophobia. Homophobia is a social, historical, community, family, and religious construction, which, sustained by misogynistic and sexist ideals, strengthens heteronormative ideas that impose relationships of power and knowledge about the sexes 24 . One study that investigated the homophobic conceptions of adolescents found moderate tolerance to homosexuality 25 obtidos pelo uso de uma escala Likert, foram analisados por uma técnica estatística multivariada.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação a iniciação da vida sexual dos adolescentes, no qual é caracterizada pela aceitação de sua orientação sexual. No qual podemos levar em consideração que pode haver o aspecto da pressão social influenciando nas suas escolhas, muitas vezes buscando a aceitação social (RONDINI et al, 2017).…”
Section: Atosunclassified
“…Chamamos a atenção para o elevado número de porcentagem favorável referente a homofobia interiorizada, a qual é caracterizada pelo fato de o adolescente poder vir a se confundir por uma pessoa homossexual, por mesmo que ele não seja, cria um receio que seja confundido como um, demonstrando um grau de homofobia, no qual o adolescente contenha seus desejos para que esteja dentro do padrão de normalidade (RONDINI et al, 2017). Muitos acreditam que a orientação sexual é uma escolha, segundo Sedgwick (2007), esboçando uma reflexão sobre a epistemologia do armário, cita que o "armário" é como um dispositivo de regulação da vida de gays e lésbicas que concerne, também, aos heterossexuais e seus privilégios de visibilidade e hegemonia de valores do sexo.…”
Section: Atosunclassified
See 1 more Smart Citation
“…Como se poderia esperar, a escola aparece como ambiente hostil e inadequado para atender a população trans. Pesquisas demonstram como a violência contra homossexuais, travestis e transexuais é percebida como violência de baixa intensidade pelos estudantes (Bento, 2011;Rondini, Teixeira Filho, & Toledo, 2017) e como a Escola trata da evasão de suas vítimas como algo "natural" e inevitável (Bento, 2011;Franco, 2016). Também ficam evidentes os "nós" do uso do nome social e de banheiros adequados ao gênero autopercebido (Torres & Vieira, 2015;Alves & Moreira, 2015).…”
Section: Identificou-se Rotas Nacionais Cujas Vítimas São Origináriaunclassified